Systematic review and meta-analysis on volume-outcome relationship of abdominal surgical procedures in Germany - Hendricks, Anne; Diers, Johannes; Baum, Philip; Weibel, Stephanie; Kastner, Carolin; Müller, Sophie; Lock, Johan Friso; Köhler, Franziska; Meybohm, Patrik; Kranke, Peter; Germer, Christoph-Thomas; Wiegering, Armin (International journal of surgery, 2021)
Background - In the past, for a number of abdominal surgical interventions a correlation between treatment volume of a hospital and the patient's outcome was shown in national and international studies. - Methods - Based on a systematic literature search we analyzed the absolute and risk-adjusted in-house lethality as well as the rate of complications and the failure to rescue after abdominal surgery in Germany. The hospitals were grouped in quintiles according to the volume of treatment. - Results - 11 studies including more than 2 million patients were identified and surgeries for the treatment of 9 disease conditions were studied. The meta-analysis shows a significantly lower absolute and risk-adjusted in-house mortality for surgery in hospitals with high treatment volumes compared to low volume hospitals. In the context of subgroup analysis, this effect is demonstrated especially for complex surgical procedures. The failure to rescue in patients suffering from sepsis is significantly lower in high volume centers compared to low volume centers. - Conclusion - This systematic review and meta-analysis shows on more than 2 million patients that there is a volume-outcome relationship for the surgical treatment of abdominal diseases in Germany across various organ systems, which is particularly true for complex interventions.